RUSSIA’S DEVELOPMENT UNDER SANCTIONS - E. I. Galeyeva (Russian Journal of Economics and Law)
Objective: to examine the socio-economic aspects of the Russian economy development under sanctions, to analyze the macroeconomic indicators and to develop a forecast of their development for the period from 2015 till 2020. Methods: the research is based on the following methods: analysis and synthesis, logical approach to the assessment of economic phenomena, synergetic model with elements of statistical, regression and variation methods. Results: using the synergetic model, the control parameters of the socio-economic system were defined and the forecast was made of Russia's macroeconomic indicators development for the period from 2015 till 2020 under financial and economic crisis. Scientific novelty: the development of scientifically grounded theoretical positions and practical recommendations in the field of analysis and forecast of macroeconomic indicators of Russia’s socio-economic development for the period from 2015 till 2020. Practical value: managers at all levels are offered tools for conducting factor analysis, the development of medium- and long-term forecasts of business activities, that will minimize the risks when making managerial decisions under current economic conditions.